2021
DOI: 10.3389/fonc.2021.724781
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Polyploid Giant Cancer Cells: Unique Way of Formation and Non-Negligible Characteristics

Abstract: Polyploidy is a conserved mechanism in cell development and stress responses. Multiple stresses of treatment, including radiation and chemotherapy drugs, can induce the polyploidization of tumor cells. Through endoreplication or cell fusion, diploid tumor cells convert into giant tumor cells with single large nuclei or multiple small nucleuses. Some of the stress-induced colossal cells, which were previously thought to be senescent and have no ability to proliferate, can escape the fate of death by a special w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 114 publications
0
29
0
Order By: Relevance
“…Atypia and polyploidy (seen as enlarged cells with aberrant nuclei) are morphological features of malignancy resulting from stress and accumulated genomic instability. 36 , 37 We previously showed that silencing Rabl6 in cultured mouse embryo fibroblasts induces genomic instability in the form of centrosome amplification and multinucleation. 24 Using mouse MPNST cell lines derived from wild-type mice with NC or NP tumors, we evaluated the effects of acute Rabl6 knockdown on both of those aberrant events ( Supplementary Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atypia and polyploidy (seen as enlarged cells with aberrant nuclei) are morphological features of malignancy resulting from stress and accumulated genomic instability. 36 , 37 We previously showed that silencing Rabl6 in cultured mouse embryo fibroblasts induces genomic instability in the form of centrosome amplification and multinucleation. 24 Using mouse MPNST cell lines derived from wild-type mice with NC or NP tumors, we evaluated the effects of acute Rabl6 knockdown on both of those aberrant events ( Supplementary Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“… 24 Using mouse MPNST cell lines derived from wild-type mice with NC or NP tumors, we evaluated the effects of acute Rabl6 knockdown on both of those aberrant events ( Supplementary Figure 3A ). Downregulation of endogenous RABL6A caused significant increases in enlarged, multinucleated cells ( Supplementary Figure 3B ) akin to polyploid giant cancer cells 36 as well as centrosome amplification ( Supplementary Figure 3C ) in both NC and NP-derived MPNST cell lines. Basal levels of centrosome amplification trended higher in cultured NP cells compared to NC cells although differences were not statistically significant ( Supplementary Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Hence, efforts have been made on searching for alternatives to generate polyploid cancer cells at laboratory scale. [14][15][16][17] In particular, the type known as Polyploid (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…42°C) have been also reported as traditional strategy to stimulate their rising. [14][15][16][17] However, it is important to note that none of these stimuli properly resemble the conditions sensed by cancer cells located inside primary tumors. Thus, with the purpose to stimulate the formation of polynucleated cells in milieus resembling the biophysical properties already described for malignant tissues, other strategies have been tested.…”
Section: Introductionmentioning
confidence: 99%